A study on the structures of the substituted (aminomethyl) lithium and (thiomethyl) lithium compounds - Hatipoglu, A; Selçuki, C; Aviyente, V; Çinar, Z (SPRINGER-VERLAG, 2002)
The structures of substituted (aminomethyl) lithium and (thiomethyl) lithium compounds have been examined. Geometric parameters, charge densities, bond orders, dipole moments and heats of formation for all the members of the two series of monomers and dimers of the units LiCN(R)(2) and LiCSR where R=H, CH3(Me), C6H5(Ph) have been calculated. The structures of the three complex compounds containing the same units; [{Li(CH2SMe)(THF)}(infinity)], [Li-2(CH2SPh)(2)(THF)(4)] and [Li-2(CH2NPh2)(2)(THF)(3)] have also been modeled. Geometry optimizations have been performed with the semi-empirical PM3 method. The molecular orbital calculations have been carried out by a self-consistent field method using the restricted Hartree-Fock formalism. Comparisons have been made with the corresponding properties of methyl lithium monomer and dimer. The results show that in all of the nitrogen-containing monomers, the C-Li bonds weaken and the Li-C-H(N) angles decrease due to the coordination of lithium with nitrogen. Substitution of hydrogen atoms by methyl or phenyl groups decreases the Li-N coordination. In the sulfur-containing compounds, sulfur behaves similarly to nitrogen but the changes are smaller because the 3p lone-pair orbital of sulfur is higher in energy than the 2p lone-pair of nitrogen. All the dimers of nitrogen/sulfur-containing methyl lithium derivatives form six-membered rings in which the Li-N( S) coordination is greater than the one in the corresponding monomers. Dimerization reactions have been found to be exothermic and the formation of all the dimers is favored. The results obtained for the three complex structures are comparable to the experimental results reported in the literature.
Keywords: (aminomethyl) lithium compounds; (thiomethyl) lithium compounds; organolithium compounds; substituted methyl lithium monomers; substituted methyl lithium dimers; TRANSITION-METAL-COMPOUNDS; SEMIEMPIRICAL METHODS; OPTIMIZATION; PARAMETERS; CARBENOIDS; COMPLEXES; PM3; Biochemistry & Molecular Biology; Biophysics; Chemistry; Computer Science